The diversity of soil insects in rice field ecosystems - Sumah, Astrid Sri Wahyuni; Kusumadinata, Ali Alamsyah (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2023)
Soil insects live in the soil or even both on the surface of the soil. Soil surface insects are one of the important animals in the soil ecosystem because their role is very important in the survival of the vegetation above them. Soil insects act as decomposers of organic materials, which will be useful as nutrients for plants. Apart from that, soil insects can also be used as indicators of soil fertility. The aim of this research is to determine the diversity of soil insects in the rice field ecosystem of Palembang City. This research was conducted in a rice field ecosystem using the pitfall trap method, 4 traps for 30 days. The results of the research obtained 14 species of soil insects from 11 families and the diversity index level of soil insects was classified as medium with a diversity index value of 1.057 with the dominating species, namely Camponotus laevigatus (Hymenoptera: Formicidae). Soil insects are an important part of an ecosystem or habitat. The diversity of ground surface insects and ecosystem functions show a very complex relationship and not much is known with certainty. A decrease in diversity and changes in the role of ground surface insects will occur due to changes in land use systems and habitats that are degraded due to development. The level of soil insect diversity needs to be maintained or increased to ensure soil fertility and overall ecosystem health and function remain optimal.